Expert project management system (EPMS): system server / Norfarazua Mohd Jaafar - Mohd Jaafar, Norfarazua (2013)
Project management is crucial for project manager and his team member to keep track of their project's progress. Sometimes a project manager can hold many project under his hand and it is hard to manage without a proper application. Even though there are many kind of project management system to guarantee the project management. The existing project management system application for Android has certain drawbacks because the application loads quite slow and always hangs. Apart from that, from the user reviews, there are some who commented that the application system could not manage users. Due to these drawbacks, this paper describes expert project management system (EPMS). In this system, a system server will be developed to cater the problems that occur. Besides that, this system will be developed on a web-based with a database by using MySQL and PHP scripting language to generate the system's interface. Experimental findings show the effectiveness in speed and easy to use system for expert project management system